Community-level relationships between prime age mortality and rural welfare: Panel survey evidence from Zambia - Jayne, Thomas S.; Chapoto, Antony; Byron, Elizabeth; Ndiyoi, Mukelabai; Hamazakaza, Petan; Kadiyala, Suneetha; Gillespie, Stuart (International Food Policy Research Institute, 2005)
Governments and development agencies require accurate information on the impacts of increased mortality rates caused by AIDS on the agricultural sector and rural livelihoods. Several previous studies have estimated the effects of prime-age mortality on afflicted households in relation to non-afflicted households. Given that HIV prevalence rates exceed 15-20 percent in many parts of southern Africa, we question whether non-afflicted households are a valid control group in hard-hit communities because non-afflicted households may nevertheless be adversely affected by the mortality occurring in neighboring households. Using nationally representative household panel data from rural Zambia, we measure the effects of prime-age adult mortality rates on changes in a set of community level welfare indicators. We find that a rise in community mortality rates from zero to 24.4 percent (which is the difference in mortality rates between the 25th and 75th percentile of all 393 communities) is associated with a 5 percent decline in the land area cultivated at the community level. We find little evidence that cropped area is shifting toward labor-saving crops such as cassava in hard-hit areas as is sometimes contended. Other factors related to agricultural policy need to be considered when examining the impact of HIV/AIDS on the agricultural sector. Most notably, many countries in eastern and southern Africa had formerly implemented state-led maize promotion policies featuring pan-territorial producer prices, major investments in marketing board buying stations, and subsidies on fertilizer distributed on credit to small farmers along with hybrid maize seed. These maize marketing policies in Zambia were either eliminated or scaled back significantly starting in the early 1990s as part of economy-wide structural adjustment programs. These policy changes clearly reduced the financial profitability of growing maize in the more remote areas where maize production was formerly buoyed by pan-territorial pricing, and has shifted cropping incentives toward other food crops such as cassava (Jayne et al).